2023
DOI: 10.1002/adma.202210665
|View full text |Cite
|
Sign up to set email alerts
|

Iridescence from Total Internal Reflection at 3D Microscale Interfaces: Mechanistic Insights and Spectral Analysis

Abstract: An experimental investigation and the optical modeling of the structural coloration produced from total internal reflection interference within 3D microstructures are described. Ray‐tracing simulations coupled with color visualization and spectral analysis techniques are used to model, examine, and rationalize the iridescence generated for a range of microgeometries, including hemicylinders and truncated hemispheres, under varying illumination conditions. An approach to deconstruct the observed iridescence and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(39 citation statements)
references
References 21 publications
0
39
0
Order By: Relevance
“…Half of the structures were masked during the dye evaporation to create a sample that was half-coated with the dye to facilitate direct comparison. Black pigmented silicone (n2=1.41) was then coated onto the back of the microstructures to reduce the refractive index contrast at the TIR interface, which enhances the color vibrancy; the black pigmentation also helps to reduce stray light scattered from behind the structures 12 . For the refractive indices used (n1=1.58, n2=1.41) and the range of incidence angles (θ) we anticipate for the structure shown in Figure 1b with illumination from the normal, we estimate dp to be on the scale of 100 to 500 nm for visible wavelengths (λ=400 to 700 nm).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Half of the structures were masked during the dye evaporation to create a sample that was half-coated with the dye to facilitate direct comparison. Black pigmented silicone (n2=1.41) was then coated onto the back of the microstructures to reduce the refractive index contrast at the TIR interface, which enhances the color vibrancy; the black pigmentation also helps to reduce stray light scattered from behind the structures 12 . For the refractive indices used (n1=1.58, n2=1.41) and the range of incidence angles (θ) we anticipate for the structure shown in Figure 1b with illumination from the normal, we estimate dp to be on the scale of 100 to 500 nm for visible wavelengths (λ=400 to 700 nm).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported a design principle for generating iridescent structural color from interference which occurs between light rays undergoing different multibounce trajectories of total internal reflection (TIR) in a microstructure 11 . Light that interferes by this mechanism can reflect by TIR many times within the microstructured cavity, with the specific ray trajectories determined by the interface geometry, refractive index, and illumination angle [11][12][13] . Previous research has thus shown that the coloration from TIR interference can be tuned by changing parameters such as the microstructure's geometry (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations